Operational challenges of engaging development partners in district health planning in Tanzania - James C. Kiologwe; Ukio Kusirye; Axel Hoffman; Albino Kalolo (BMC, 2022)
Abstract Background Development Assistance for Health (DAH) represents an important source of health financing in many low and middle-income countries. However, there are few accounts on how priorities funded through DAH are integrated with district health priorities. This study is aimed at understanding the operational challenges of engaging development partners in district health planning in Tanzania. Methods This explanatory mixed-methods study was conducted in Kinondoni and Bahi districts, representing urban and rural settings of the country. Data collection took place between November and December 2015. The quantitative tools (mapping checklist, district questionnaire and Development partners (DPs) questionnaire) mapped the DPs and their activities and gauged the strength of DP engagement in district health planning. The qualitative tool, a semi-structured in-depth interview guide administered to 20 key informants (the council health planning team members and the development partners) explained the barriers and facilitators of engagement. Descriptive and thematic analysis was utilized for quantitative and qualitative data analysis respectively. Results Eighty-six per cent (85%) of the development partners delivering aid in the studied districts were Non-Governmental Organizations. Twenty percent (20%) of the interventions were HIV/AIDS interventions. We found that only four (4) representing 25 % (25%) DPs had an MOU with the District Council, 56 % (56%) had submitted their plans in writing to be integrated into the 2014/15 CCHP. Six (6) representing 38 % (38%) respondents had received at least one document (guidelines, policies and other planning tools) from the district for them to use in developing their organization activity plans. Eighty-seven point 5 % (87.5%) from Bahi had partial or substantial participation, in the planning process while sixty-two point 5 % (62.5%) from Kinondoni had not participated at all (zero participation). The operational challenges to engagements included differences in planning cycles between the government and donors, uncertainties in funding from the prime donors, lack of transparency, limited skills of district planning teams, technical practicalities on planning tools and processes, inadequate knowledge on planning guidelines among DPs and, poor donor coordination at the district level. Conclusions We found low engagement of Development Partners in planning. To be resolved are operational challenges related to differences in planning cycles, articulations and communication of local priorities, donor coordination, and technical skills on planning and stakeholder engagement.